2017
DOI: 10.1007/s11356-017-8590-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of meteorological factors and acute stroke events in Kaunas (Lithuania) in 2000–2010

Abstract: Some researchers have hypothesised that meteorological factors may have an impact on acute cerebrovascular diseases. The aim of this study was to determine an impact of some meteorological factors on occurrence of acute cerebrovascular events in the middle-aged Kaunas population. Kaunas stroke register data were used. Data on meteorological factors for the time period from 2000 to 2010 were obtained from the Lithuanian Hydrometeorological Service Kaunas Meteorological Station. We analysed 4038 cases with strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
2
13
2
Order By: Relevance
“…Contrary to the findings reported by other researchers [14][15][16][17][18][19][20][21][22][23], the current study did not confirm effects of environmental factors investigated, i.e., air temperature, atmospheric humidity, speed of wind, pressure and total daily precipitation in the incidence of cardiac events, either on halny days or on days preceding the onset of halny, as well as throughout the whole year in the consecutive months from January 2011 to December 2011. The findings showed no statistically significant correlations between the environmental variables and the number of cardiac events in any of the periods analysed (i.e., days with halny, days preceding halny onset, total days with and preceding halny, other days, all the days combined.)…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to the findings reported by other researchers [14][15][16][17][18][19][20][21][22][23], the current study did not confirm effects of environmental factors investigated, i.e., air temperature, atmospheric humidity, speed of wind, pressure and total daily precipitation in the incidence of cardiac events, either on halny days or on days preceding the onset of halny, as well as throughout the whole year in the consecutive months from January 2011 to December 2011. The findings showed no statistically significant correlations between the environmental variables and the number of cardiac events in any of the periods analysed (i.e., days with halny, days preceding halny onset, total days with and preceding halny, other days, all the days combined.)…”
Section: Discussioncontrasting
confidence: 99%
“…Based on a review of the literature it can be concluded that many researchers are investigating the association between wind-related environmental variables, and cardio-or cerebrovascular events, including the impact observed on days preceding onset of such weather conditions [14][15][16][17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arterial ischemic stroke in our patients appeared most frequently in winter (34%), then au- tumn (23%) and in summer and spring with the same frequency (22%). In adults, low ambient temperature of the day of stroke onset increased the risk of ischemic stroke as well as high-speed wind, especially in older patients [21]. Higher frequency of stroke in winter or autumn may also be linked with the greater frequency of infections, which are common in the colder seasons of the year.…”
Section: Ais -Arterial Ischemic Stroke Laci -Lacunar Anterior Circulmentioning
confidence: 99%